Granulomatous Hypophysitis due to Wegener’s Granulomatosis - Goyal, Mayank; Kucharczyk, Walter; Keystone, Edward (American Journal of Neuroradiology, 2000)
Summary: We describe the MR imaging findings in a case of granulomatous hypophysitis due to Wegener’s granulomatosis. A high index of suspicion of hypophysitis based on imaging findings allowed successful medical management and helped avoid surgery. The MR imaging features included a thickened stalk, a diffusely and uniformly enlarged gland, a normal size or minimally enlarged sella, and enhancement of the optic chiasm.